The body(sattva) on the cross: comparative theological investigation of the theology of the cross in the light of Chinese Mahayana suffering bodhisattvas - Hedges, Paul (2023)
This paper explores ways that the suffering figure of Jesus on the cross has conceptual overlap with some Chinese Buddhist images of bodhisattvas. While the suffering saviour motif is often contrasted with staid and placid Buddha and bodhisattva images, it is argued that suffering is at least implicit in the stories associated with such figures as Guanyin and Dizang, including self-mutilation. Looking at contemporary theories of pain and suffering, areas of mutual interaction between Jesus and some Chinese bodhisattva figures are explored.